Role of building surveyor in public works department : challenges and trend in future / Amir Zafuan Arif Zulkefli - Zulkefli, Amir Zafuan Arif (Faculty of Architecture, Planning and Surveying, 2010)
In recent years, the issues of maintenance of government buildings are always reported by the media. The weakness of the government in managing the assets causes impact to the public. After the incident involving injury to the publics, the government began to seriously to find solution in manage the maintenance and facility in properly. This provides an opportunity to develop profession Building Surveyors are already trained in maintenance management. The government created the position of Building Surveyor in the Public Works Department for manage the problems existed. The study was conducted to identify the challenges faced by the Building Surveyor in the Public Works Department after they were given the opportunity to prove their ability in dealing with maintenance issues. How far the Building Surveyors which could go a long way in this field have an impact or whether it can develop and thus provide advantages and benefits to the public